Analysis the Application of Public Health Protocols of Covid 19 in Malang City, East Java, Indonesia - Susilo Bekti; Mistianah Mistianah; Tria Muhamad Aris; Ardian Anjar Pangestuti; Yati Yati (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
Cases of Covid 19 infection have spread to almost all parts of Indonesia country. The government has issued a policy regarding the implementation of health protocols in order to carry out daily activities to reduce the transmission rate. This study aims to identify the implementation of public health protocol during the Covid 19 pandemic in Malang, East Java, Indonesia. This research is a descriptive quantitative research. Data analysis in this study uses univariate analysis. The population in this study is the citizens of Malang city as many as 137.367 people with a sample of 100 respondents. The data was taken by a questionnaire consisting of data on the characteristics of the respondents and their behavior. The data was collected using purposive sampling. The results of the study indicate that public knowledge is in the good category as much as (75%) the public attitude is in the sufficient category (60%) and the public actions are in the sufficient category (66%).